Safety profile of an 8F femoral arteriotomy closure using the Angio-Seal device in thrombolysed acute stroke patients undergoing thrombectomy. Issue 5 (October 2018) - Wareham, James; Luppe, Sebastian; Youssef, Adam; Crossley, Robert; Mortimer, Alex
Background: The relationship between bridging thrombolysis and femoral access site complications after mechanical thrombectomy remains contested. Use of a closure device could minimise bleeding complications. This study aimed to elucidate the rate of access site complications in a cohort of patients treated using an 8F groin sheath with subsequent closure using the Angio-Seal to assess safety and the impact of bridging thrombolysis on access site complication rate. Methods: All patients with large vessel occlusive stroke treated between 2014 and 2017 with thrombectomy with or without bridging thrombolysis were reviewed. A prospectively acquired departmental database was used to obtain baseline data, and the radiology information and haematology reporting systems were used to record imaging or transfusion relating to subsequent access site complications. Results: Seventy-five patients treated with thrombectomy alone were compared to 70 patients treated with prior intravenous thrombolysis. All had an 8F femoral sheath placed for arterial access, and all underwent attempted haemostasis with an 8F Angio-Seal. Two patients (1.14%) suffered Angio-Seal device failure necessitating manual pressure. One patient (0.6%) suffered a small femoral pseudo-aneurysm. No retroperitoneal haemorrhage, haematoma requiring transfusion, ipsilateral deep-vein thrombosis or ipsilateral acute limb ischaemia was encountered. There was no significant difference in the rate of haemorrhagic, ischaemic or infective complications between those treated with bridging thrombolysis or thrombectomy alone. Conclusion: Use of the Angio-Seal closure device for 8F femoral access is safe in acute stroke patients. Intravenous thrombolysis prior to endovascular thrombectomy does not significantly alter femoral access site complication rate if this approach is used.